Respon Pertumbuhan, Produksi Dan Kadar Fosfor Daun Terhadap Pemberian Dolomit Dan Pupuk Npk Pada Kacang Kedelai (Glycine Max (L.) Merril) Pada Tanah Ultisol - Pandiangan, Samse; Tampubolon, Bangun; Naibaho, Benika; Lumbangaol, Jualiana (LPPM Universitas HKBP Nommensen, 2021)
The objectives of this study was to observe the effect of dolomite and NPK fertilizer application on growth, yield and leaf phosphorus levels of soybeans (Glycine max (L.) Merril) due to the application of dolomite and NPK fertilizers. This research was conducted from June 2019 to December 2019, at the Experimental Station of Agriculture Faculty of University of HKBP Nommensen Medan in Simalingkar B Village, Medan Tuntungan District at an altitude of ±33m above sea level. Soil type Ultisol with Tex-sand 43.75%, Tex-dust 42.18%, Tex-clay 14.07; pH 4.63; cation exchange capacity (CEC) 14.64%, Ptotal 0.10%, N kjehldahl 1.9% K-exch 0.20%, Ca-exch 1.32%, Mg-exch 0.92%. This research was arranged in a factorial randomized block design (RAK) with 2 treatment factors, namely, the first factor was dolomite (D) which consisted of 3 levels, namely: D0 = 0 g/polybag, D1 = 11.2 g/polybag, D2 = 22.4 g/polybag. The second factor was NPK fertilizer (N), which consisted of 4 levels, namely: N0 = 0 g/polybag, N1 = 1.5g/polybag, N2 = 3 g/polybag and N3 = 4.5g/polybag. Parameters observed were plant height, number of leaves, number of pods, number of filled pods, weight of filled pods, dry seed production per plant, dry weight of 100 seeds and leaf phosphorus levels. The results showed that dolomite application had a very significant effect on the number of pods, number of filled pods, weight of filled pods, dry seed production per plant, dry weight of 100 seeds, but had no significant effect on plant height, number of leaves and leaf phosphorus levels. The application of NPK fertilizer had a very significant effect on the number of pods, number of filled pods, dry seed production per plant, dry weight of 100 seeds but had no significant effect on plant height, number of leaves, weight of filled pods and leaf phosphorus content. The interaction of dolomite and NPK fertilizer had no significant effect on all observed parameters.